3(x+2)=7(x-1)+11

Simple and best practice solution for 3(x+2)=7(x-1)+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=7(x-1)+11 equation:


Simplifying
3(x + 2) = 7(x + -1) + 11

Reorder the terms:
3(2 + x) = 7(x + -1) + 11
(2 * 3 + x * 3) = 7(x + -1) + 11
(6 + 3x) = 7(x + -1) + 11

Reorder the terms:
6 + 3x = 7(-1 + x) + 11
6 + 3x = (-1 * 7 + x * 7) + 11
6 + 3x = (-7 + 7x) + 11

Reorder the terms:
6 + 3x = -7 + 11 + 7x

Combine like terms: -7 + 11 = 4
6 + 3x = 4 + 7x

Solving
6 + 3x = 4 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + 3x + -7x = 4 + 7x + -7x

Combine like terms: 3x + -7x = -4x
6 + -4x = 4 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + -4x = 4 + 0
6 + -4x = 4

Add '-6' to each side of the equation.
6 + -6 + -4x = 4 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = 4 + -6
-4x = 4 + -6

Combine like terms: 4 + -6 = -2
-4x = -2

Divide each side by '-4'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -19-(-13)= | | -4x+2(3x-1)-12=0 | | 6x+7(x+17)=184 | | -28+11= | | -1x+7=1-3x | | 2x+46=17+5x | | -7x-3(-4x+13)=11 | | -34+43= | | 7/8(3/5) | | y=-(x^2+4x-9) | | 7x-(3x-6)-2=20 | | 9x^2+18x-40x=0 | | v-8=16+4v | | 25x-(6x-12)= | | 7m-5m+3m-3m=46 | | 3(n+2)+(n*0.5)=2(n+1)-14 | | 18-6u= | | 34-(34)= | | 7g+14+-5g=-8 | | 4r-r-3r+r=11 | | -8w=-144 | | (34+11)+9=(11+34)+9 | | 5x-2(-x-11)=78 | | 10p-2(3p-6)=4(5p-6)10p | | x^3-6x^2-12x=0 | | 2x+10000=497500 | | 2.4x+11.3=3.7-0.6x | | 3/4x-12=1/4x-9 | | 0.3x+-0.2x=2 | | -9(7)= | | 32x^2/990^2 | | 164=6x-4(-4x+3) |

Equations solver categories